Stenting for Emergency Colorectal Obstruction: An Analysis of 204 Patients in Relation to Predictors of Failure and Complications. (September 2015) - Köhler, G.; Antoniou, S. A.; Lechner, M.; Mayer, F.; Mair, J.; Emmanuel, K.
Background and Aims: Self-expanding metallic stents are increasingly used in the management of malignant and benign colorectal obstructions. We aimed to identify relevant predictive factors for stent failure and stent-related complications. Material and Methods: We conducted a retrospective single-center analysis of 204 consecutive patients who underwent emergency colorectal stenting procedures because of symptomatic bowel obstructions from 1996 to 2011 at the Sisters of Charity Hospital Linz, Austria. Results: A total of 204 patients (median age 74 years) with 36 (17.7%) benign and 168 (82.3%) malignant obstructions were included in the study. Technical success was achieved in 92.5% and clinical success in 86.8% of the cases. Major complications occurred in 2.9% and minor ones in 19.6%. Overall mortality during a median follow-up period of 4.3 years was 73% (149 patients). Relevant predictors of increased risk of complications were extracolonic obstruction (p = 0.001), complete obstruction (p = 0.066), and inflammatory bowel disease (p = 0.05). Stent localization at the splenic flexure, a stenosis of >8 cm in length, and the need for endoscopic guidance were associated with higher rates of technical and/or clinical stenting failure. Conclusion: Colorectal stenting is less invasive than other means of emergency treatment for large bowel obstruction; it is generally safe and effective in different types of colorectal obstruction. However, relevant rates of failure and complications were recorded and predictors could be determined.